2011
DOI: 10.1016/j.ajpath.2010.10.024
|View full text |Cite|
|
Sign up to set email alerts
|

Bone Marrow–Derived Progenitor Cells Do Not Contribute to Podocyte Turnover in the Puromycin Aminoglycoside and Renal Ablation Models in Rats

Abstract: A key event in the progression of glomerular disease is podocyte loss that leads to focal and segmental glomerulosclerosis (FSGS). Because adult podocytes are postmitotic cells, podocyte replacement by bone marrow-derived progenitors could prevent podocytopenia and FSGS. This study uses double immunofluorescence for Wilms' tumor-1 and enhanced green fluorescent protein (eGFP) to examine whether an eGFP-positive bone marrow transplant can replace podocytes under normal circumstances and in 3 different rat model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…101 Although bone marrow-derived cells have been postulated to give rise to podocytes, 102 lineage tracing studies indicate that these cells likely do not contribute substantially to podocyte regeneration. 103 …”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…101 Although bone marrow-derived cells have been postulated to give rise to podocytes, 102 lineage tracing studies indicate that these cells likely do not contribute substantially to podocyte regeneration. 103 …”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…38 Bone marrow derived stem cells are not podocyte progenitors in two experimental models. 39 Some studies in humans have suggested that PECs may serve this podocyte progenitor role and repopulate the glomerulus following podocyte loss 38,39 , although this remains controversial, as similar paradigms do not exist in adult mice. 40 (see below).…”
Section: Podocyte Depletion Is Required For the Development Of Classimentioning
confidence: 99%
“…PAN was induced in Sprague-Dawley rats by intraperitoneal injection of puromycin aminonucleoside in PBS (Sigma-Aldrich) as described. 52 Puromycin aminonucleoside induces severe proteinuria and glomerular ultrastructural changes in rats by direct injury of the podocyte cytoskeleton, 53 leading to sustained foot-process effacement, podocyte loss, glomerular sclerosis, and proteinuria resembling human FSGS. Animals were euthanized on day 14, 18, 28, 35 (PHN), or 28 (PAN) for additional analyses when persistent injury with morphologic changes, such as focal sclerosis in PAN and podocyte swelling and loss in PHN, was established.…”
Section: Animal Experimentsmentioning
confidence: 99%